Leptin, CD4+ Treg and the prospects for vaccination against H. pylori infection - Walduck, Anna K.; Becher, Dorit (Frontiers in Immunology, 2012)
H. pylori infection induces chronic inflammation which is characterised not only by infiltrations of inflammatory cells such as Neutrophils and CD4+ T cells, but also significant populations of regulatory T cells (Treg). These cells are important for disease pathogenesis because they are believed to contribute to the persistence of the infection. Despite encouraging results in animal models, the prospects for an effective H. pylori vaccine are currently poor because of generally disappointing results in preclinical and Phase 1 trials. As a result, a current major focus of basic research on vaccination is to better understand the mechanisms regulating the inflammatory response with the view it can inform future vaccine design. Our studies in this area have focussed on gastric CD4+Treg in vaccinated mice, and raised the hypothesis that adipokines in particular leptin are involved the establishment of a protective gastric immune response. Here we discuss the hypothesis that vaccination deregulates Treg responses in the gastric mucosa, and that this process is mediated by leptin. We propose that reduced suppression permits a protective sub population of H. pylori specific CD4+ T cells to exert protective effects, presumably via the gastric epithelium. Evidence from the literature and experimental approaches will be discussed.